The development of a survey instrument for measuring a relationship between statistical process control success factors and performance - Mohd. Rohani, Jafri; Mohd. Yusof, Sha’ri; Mohamad, Ismail (Faculty of Mechanical Engineering, 2010)
The present study highlights the instrument development to measure the relationship between statistical process control success factors construct and performance construct. From an extensive review of literature of statistical process control implementation, eleven dimensions of statistical process control success factors and three dimensions of performance were identified. In this paper, a survey instrument to measure SPC success factors construct associated with quality and firm performance was proposed. The reliability and validity of this survey instrument were tested using data from 122 respondents. It was concluded that instrument developed in this paper has satisfactory psychometric properties, reliable and valid. Hence the researcher can use this survey instrument to build the model to find the relationship between statistical process control success factors construct and performance construct. Industrial practitioners can use this survey instrument to identify and predict the success of their SPC implementation projects through managing of these associated factors.